Innovative Approaches To Enhancing Student Engagement In Science: Games-Based Learning Initiative - Fitri, Kurniawaty; Fanni, Aria Dwi; Puspita, Tiara; Marini, Dewi Santi; Sinaga, Abdul Hamid; Zahara, Alya; Prakusuma, Bayu; Annistasya, Indah; Erlangga, Pemas Putra; Nabila, Putri; Diva, Tinezia Mir’atul (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service initiative focuses on improving student engagement and learning outcomes in science education at SMPN 5 Ukui through the application of game-based learning models. Conducted over two sessions in July 2024, the program employed the Number head together and Team Games Tournament methods to foster active participation and enhance students' understanding of the material. Despite challenges such as limited facilities, the initiative successfully increased student interest and involvement in learning science. The program demonstrated that game-based learning can be an effective tool for transforming traditional teaching methods, particularly in rural schools with limited resources. The results indicate a positive impact on student motivation and academic performance, suggesting the potential for broader implementation in similar educational settings. The initiative underscores the importance of innovative teaching approaches in achieving educational goals and highlights the need for continued support and resources to ensure the sustainability and scalability of such programs in the future.